Optimization of Engineering Properties and XRD Pattern of the Conventional Brick by Recycling the Discarded Cigarette Butts - Shoaib Muhammad; Zeeshan Ahmad; Muhammad Abdur Rehman Hamid; Waqas ur Rahman; Talha Saleem; Muhammad Jahangir Khan (Journal of ICT, Design, Engineering and Technological Science, 2023)
Cigarette butts are one of the integral pollutants that severely crank the major public spots like streets, roadsides, seashores, river canals, etc. Apart from this, they have a secondary effect in which they provide space for other trash materials. If they are not properly disposed of then they will slowly burn for an out three hours. Thousands of kilograms of harmful waste are created annually from a few tones of cigarettes produced worldwide. Because cellulose acetate filters are not very biodegradable, Cigarette Butts (CBs) accumulate in the environment. A portion of the findings from an ongoing study on repurposing cigarette butts into baked clay bricks are presented in this report. Cigarette butts have been utilized to make bricks for this project. Based on the test findings, the bricks' compressive strength was found to be 37%, 53.2%, and 79.7% lower than that of typical bricks, with CB percentages of 4, 8, and 12, respectively. Also, water absorption of the brick was increased by 8%, 16%, and 48 % with CB percentages 4, 8, and 12 respectively than normal brick water absorption. Thermal conductivity of bricks was also reduced with using CBs much in amount and thermal insulation was improved by almost 50% on 4% of CBs dosage which is the optimum percentage. XRD pattern shows the Sio2 quartz in maximum with some other ingredients like feldspar, hematite and orthoclase, etc. means that the results revealed amounts of heavy metals.